Analisis Ilmiah Rumput Fatimah dalam Perspektif Islam dan Pengobatan Herbal Tradisional - R. Nadhiva Ratu Aulia; Bintang Rizki Amanda; Nabilla Yuanintika Syisya Rahmudi (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Fatimah grass (Labisia pumila) is a herbal plant that is widely known in traditional medicine, especially in Southeast Asia. This plant is believed to have various medical properties and has been used to treat various health problems, especially during the birthing process for pregnant women. Clinical studies show the potential of Fatimah Grass in improving women's reproductive health and balancing hormone levels. Although many benefits have been identified, further research is needed to understand the mechanism of action, optimal dosage, and potential side effects. This article aims to summarize the benefits and potential of Fatimah Grass in the medical field and encourage further research for scientific validation and clinical application.